Impact of ADC parameters on nonlinear compensation performance in 200 Gb/s polarization-multiplexed QAM transmission - Lin, Chien-Yu; Schmauß, Bernhard (IEEE Photonics Conference (IPC), 2013)
Nonlinear compensation based on digital backward propagation (DBP) is numerically implemented in 200 Gb/s polarization multiplexed (PM) PM-m-QAM un-compensated transmission. The impact of reduced ADC oversampling and quantization on DBP performance is analyzed.
lhft_intern.bib::Lin2013